2020
DOI: 10.1002/cpp.2436
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomized controlled trial of a video self‐help intervention for depression based on acceptance and commitment therapy: Feasibility and acceptability

Abstract: A common setting where depression is identified and treated is in primary care, where there is a need for low-intensity and cost-effective interventions to be used as part of a stepped-care model. The current study involved a pilot, parallel-group, randomized controlled trial of a video self-help intervention for primary care patients based on acceptance and commitment therapy (ACT). The intervention, called LifeStories, consisted of storytelling vignettes of patients describing their use of ACTconsistent copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There are two possible reasons for the low dropout rates in the present study. First, on the technical level, in addition to the vividness and high interactivity of the internet‐based treatment procedure (Gaudiano et al, 2020), the system used an automatic email sending program. Before each intervention session, the computer program automatically sent a brief reminder email to the client.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible reasons for the low dropout rates in the present study. First, on the technical level, in addition to the vividness and high interactivity of the internet‐based treatment procedure (Gaudiano et al, 2020), the system used an automatic email sending program. Before each intervention session, the computer program automatically sent a brief reminder email to the client.…”
Section: Discussionmentioning
confidence: 99%
“…Video acceptability was measured using a translated and adapted 4-item version of the acceptability and likability scale used by Gaudiano et al [ 45 ]. In total, 3 items measured overall likability, comprehensibility, and interestingness of the videos on a 5-point rating scale.…”
Section: Methodsmentioning
confidence: 99%
“…Another component of previous help seeking–facilitating strategies has been storytelling. A pilot study on a video-based intervention indicated that storytelling was well accepted and perceived as engaging [ 45 ]. In addition, an RCT evaluated internet-based storytelling programs with varying interactivity and stigma-related content.…”
Section: Introductionmentioning
confidence: 99%
“…Guided by recommendations from Leon et al (2011), the primary aim of this pilot trial was to evaluate the feasibility and acceptability of the intervention itself as well as study procedures. We set the following a priori acceptability/feasibility benchmarks for the pilot study based on the clinical trial experience from the research team and similar to other treatment development projects (Gaudiano et al, 2020(Gaudiano et al, , 2023: average recruitment of at least two participants per month, app engagement rate ≥ 75% of the participants who used the app, drop out/loss to follow-up ≤ 20%, CSQ score ≥ average 24, significant improvement on BPRS scores over time, and no serious adverse events due to study involvement.…”
Section: Statistical Analysesmentioning
confidence: 99%